Cardiovascular and renal protective effects of non-vitamin K antagonist oral anticoagulants and warfarin in patients with atrial fibrillation - Seong Huan Choi; Mina Kim; Hoseob Kim; Dae-Hyeok Kim; Yong-Soo Baek (PLoS ONE, 2022)
Aim Data on the use of non-vitamin K antagonist oral anticoagulants (NOACs) in relation to the risk of cardiovascular (CV) disease and renal protection among patients with atrial fibrillation (AF), are relatively sparse. We aimed to compare the effectiveness and safety of NOACs with those of warfarin for vascular protection in a large-scale, nationwide Asian population with AF. Methods and results Patients with AF who were prescribed oral anticoagulants according to the Korean Health Insurance Review and Assessment database between 2014 and 2017 were analyzed. The warfarin and NOAC groups were balanced using propensity score weighting. Clinical outcomes included ischemic stroke, myocardial infarction, angina pectoris, peripheral artery disease, chronic kidney disease (CKD), end-stage renal disease (ESRD), CV death, and all-cause death. NOAC use was associated with a lower risk of angina pectoris (HR, 0.79 [95% CI, 0.69–0.89] p<0.001), CKD stage 4 (HR, 0.5 [95% CI, 0.28–0.89], p = 0.02), and ESRD (HR, 0.15[95% CI, 0.08–0.32], p<0.001) than warfarin use. NOACs and warfarin did not significantly differ with respect to stroke reduction (HR, 1.05 [95% CI, 0.88–1.25], p = 0.19). NOAC use was associated with a lower risk of intracranial hemorrhage (HR, 0.6 [95% CI, 0.44–0.83], p = 0.0019), CV death (HR, 0.55 [95% CI, 0.43–0.70], p<0.001), and all-cause death (HR, 0.6 [95% CI, 0.52–0.69], p<0.001) than warfarin use. Conclusion NOACs were associated with a significantly lower risk of adverse CV and renovascular outcomes than warfarin in patients with AF.